Persepsi Tentang Beban Kerja dengan Stres Kerja pada Karyawan Pabrik Mebel - Ida Furi Sukmawati (Nur Science Institute, 2021)
Stress at work is a phenomenon that often occurs within an organization. One factor that influences work stress is the perception of workload. Poor assessment of a job will make employees less eager to work, resulting in work stress. The purpose of this study was to determine the relationship between perceptions about workload and work stress of PT. X employees. The method in this study uses quantitative methods. The research sample were 84 employees by sampling using purposive sampling techniques. Data collection methods use scale. Data analysis techniques using Product Moment analysis techniques. The product moment calculation results obtained by the correlation coefficient r (xy) = -0.266 with significance = 0.007; (p < 0.01), meaning that there is a very significant negative relationship between perceptions about workload with work stress. Effective contribution of perceptions about employee workload on work stress by 26.60%. From the results of this study it is also known that perceptions of workload and work stress are classified as high.